2013
DOI: 10.1118/1.4811099
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for reliable time‐resolved dosimetry of electronic portal imaging devices for fixed‐gantry IMRT and VMAT

Abstract: Purpose:The continuous scanning mode of electronic portal imaging devices (EPID) that offers time-resolved information has been newly explored for verifying dynamic radiation deliveries. This study seeks to determine operating conditions (dose rate stability and time resolution) under which that mode can be used accurately for the time-resolved dosimetry of intensity-modulated radiation therapy (IMRT) beams. Methods: The authors have designed the following test beams with variable beam holdoffs and dose rate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…4D-portal dosimetry is a very interesting recent development as it combines a high spatial and time resolution. 14,24,25 However, none of these studies have documented an analysis to identify the source of observed deviations.…”
Section: E Limitations Of Time-resolved Point Dose Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…4D-portal dosimetry is a very interesting recent development as it combines a high spatial and time resolution. 14,24,25 However, none of these studies have documented an analysis to identify the source of observed deviations.…”
Section: E Limitations Of Time-resolved Point Dose Measurementsmentioning
confidence: 99%
“…[6][7][8][9][10][11] There are only a few studies that have applied time-resolved dosimetry using an ionization chamber. [12][13][14] However, the time-resolved ionization chamber measurements in these studies were not compared to the TPS calculated dose but either used to investigate reproducibility of the dose delivery or to benchmark time-resolved measurements using a 3D detector array. In contrast, the current study compares the measured dose and the TPS calculated dose, includes a significantly larger dataset, and intends to identify the source of observed deviations.…”
Section: Introductionmentioning
confidence: 99%
“…Linearity is the reduction of central pixel value/MU normalized to the value for the maximum MU of irradiation for each beam. [ 3 ] Further analysis was conducted to evaluate the number of acquired cine images in each MU delivery with different dose rates and a constant frame rate. The number of images acquired in each MU delivery was normalized to the maximum MU setting.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…[ 2 ] Since cine mode is synchronized to beam pulses, the frame acquisition rate depends on dose rate. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation